Impact of the COVID-19 Pandemic on Mental Well-Being. A Nationwide Online Survey Covering Three Pandemic Waves in Poland - Babicki, Mateusz; Kowalski, Krzysztof; Bogudzińska, Bogna; Mastalerz-Migas, Agnieszka (Frontiers in Psychiatry, 2021)
The COVID-19 pandemic has a significant impact on human life. This study aims to assess the prevalence of depressive and anxiety symptoms and the assessment of the quality of life in different stages of the COVID-19 pandemic based on an online nationwide survey. The study was based on a voluntary, anonymous, and authors' own questionnaire. The first section assesses sociodemographic status. Then, standardised psychometric tools were used such as the Beck Depression Inventory (BDI), the Generalised Anxiety Disorder Assessment (GAD-7) and the Manchester Short Assessment of Quality of Life (MANSA). The study was conducted in three stages corresponding to the waves of the COVID-19 pandemic in Poland. The survey involved 5,790 respondents; 2,457, 1,626 and 1,707 for the first, second and third pandemic wave respectively. It was found that anxiety and depressive symptoms escalated as the pandemic progressed. There was no significant effect on the subjective quality-of-life assessment. Moreover, there was a gradual decrease in anxiety about being infected with COVID-19 as well as reduced adherence to the Minister of Health's recommendations. As the COVID-19 pandemic progressed, depressive and anxiety symptoms escalated among Poles. Women, singles and people with prior psychiatric treatment are more likely to develop the aforementioned symptoms.